Electron swarm parameters of SF6 under time varying electric fields - A. Settaouti (International Journal of Applied Power Engineering (IJAPE), 2020)
The electron swarm parameters in gases are necessary for the simulations of plasma processes. The sulfur hexafluoride (SF6) has enormous applications suitability, because of its excellent dielectric properties, it is a gas used extensively as an insulating gas in various electric devices. Consequently, we must dedicate a significant attention to studying the physical properties of this gas. An investigation has brought into effect on the electron swarms parameters in SF6 gas in time varying electric fields using a Monte Carlo simulation. Swarm parameters as a function of instantaneous E/N (E is the electric field and N the gas number density of background gas molecules) for different dE/dt are determined.